Assessing neuraxial microstructural changes in a transgenic mouse model of early stage Amyotrophic Lateral Sclerosis by ultra‐high field MRI and diffusion tensor metrics - Gatto, Rodolfo G. (Animal Model Exp Med, 2020)
OBJECTIVE: Cell structural changes are one of the main features observed during the development of amyotrophic lateral sclerosis (ALS). In this work, we propose the use of diffusion tensor imaging (DTI) metrics to assess specific ultrastructural changes in the central nervous system during the early neurodegenerative stages of ALS. METHODS: Ultra‐high field MRI and DTI data at 17.6T were obtained from fixed, excised mouse brains, and spinal cords from ALS (G93A‐SOD1) mice. RESULTS: Changes in fractional anisotropy (FA) and linear, planar, and spherical anisotropy ratios (C(L), C(P), and C(S), respectively) of the diffusion eigenvalues were measured in white matter (WM) and gray matter (GM) areas associated with early axonal degenerative processes (in both the brain and the spinal cord). Specifically, in WM structures (corpus callosum, corticospinal tract, and spinal cord funiculi) as the disease progressed, FA, C(L), and C(P) values decreased, whereas C(S) values increased. In GM structures (prefrontal cortex, hippocampus, and central spinal cord) FA and C(P) decreased, whereas the C(L) and C(S) values were unchanged or slightly smaller. Histological studies of a fluorescent mice model (YFP, G93A‐SOD1 mouse) corroborated the early alterations in neuronal morphology and axonal connectivity measured by DTI. CONCLUSIONS: Changes in diffusion tensor shape were observed in this animal model at the early, nonsymptomatic stages of ALS. Further studies of C(L), C(P), and C(S) as imaging biomarkers should be undertaken to refine this neuroimaging tool for future clinical use in the detection of the early stages of ALS.